Association between childhood asthma and attention deficit hyperactivity or autism spectrum disorders: A systematic review with meta‐analysis. Issue 2 (13th October 2020) - Kaas, Trine H.; Vinding, Rebecca K.; Stokholm, Jakob; Bønnelykke, Klaus; Bisgaard, Hans; Chawes, Bo L.
Abstract: Background: Children with asthma are at risk of depression and anxiety and growing evidence suggest they may also be at risk of attention deficit hyperreactivity disorder (ADHD) and autism spectrum disorder (ASD). Here, we conducted a systematic review with meta‐analysis of studies investigating association between asthma and ADHD or ASD in children. Methods: A comprehensive search using PubMed, EMBASE and Cochrane Library databases was completed in March 2019. Observational human studies published in English, clinic‐based or population‐based with a healthy comparator group, evaluating asthma‐ADHD or asthma‐ASD overlap in children 18 years or younger using categorical diagnoses (yes/no) were considered for inclusion. Random effects meta‐analysis models were used to analyse data. The Newcastle Ottawa Scale was used to evaluate risk of bias. Results: A total of 25 asthma‐ADHD studies were included of which 17 showed significant positive associations and one a negative association: 17/25 studies were population‐based, 19/25 were cross‐sectional or cohort studies and 7/25 had a low risk of bias. We performed a meta‐analysis of 23 of the studies, which showed a significant association between asthma and ADHD: odds ratio (OR) 1.52 (1.42‐1.63), P  < .001, I2 = 60%. All studies were adjusted for age and sex and a large proportion; that is, 19/23 were further adjusted for relevant confounders. Seventeen asthma‐ASD studies were included, whereof 7 showed a positive association and 3 a negative association; 8/17 were population‐based with a cross‐sectional study design and 4/17 had a low risk of bias. We performed a meta‐analysis of 14 of the studies, which did not show a significant association between asthma and ASD: OR 1.12 (0.93‐1.34), P  = .24, I2 = 89%. All studies were adjusted for age and sex and 10/14 were further adjusted for relevant confounders. Conclusions: This systematic review with meta‐analyses shows a significant overlap between asthma and ADHD, but not between asthma and ASD in children. Clinicians taking care of children with asthma or ADHD should be aware of such association to aid an early diagnosis and treatment of such comorbidity.